Effect of perforated low-density polyethylene films on postharvest quality of avocado fruit - Nana Millicent Duduzile Buthelezi; Tieho Paulus Mafeo (Heliyon, 2024)
Avocado (Persea americana Mill.) being a climacteric fruit, is very prone to quality deterioration and spoilage due to high metabolic activities which leads to postharvest and economic losses. The purpose of this study was to evaluate the impact of perforated low-density polyethylene (LDPE) packaging films on postharvest quality and shelf life of ‘Fuerte’ avocado. Fruit were packaged in LDPE plastics (20 and 40 μm) whereas unpackaged fruit were considered as control. Fruit were kept at ambient environments (21 ± 1 °C and 60.0 ± 5% RH) for 12 days and sampled at 4 days interval. The in-pack avocado created a suitable headspace with low O2 and high CO2 concentrations, which yielded improved preservation of postharvest quality and prolonged shelf life of the avocado. Fruit packed in both 20 and 40 μm LDPE films had lower ethylene production and respiration rates, weight loss, firmness loss, preserved fruit size, high pH, titratable acidity, low soluble solid content, sugar:acid ratio, malondialdehyde content and lipoxygenase activity compared to control. Fruit in LDPE films had no symptoms of decay (20 μm) and slight incidence and decay (40 μm) and were markable during shelf life compared to control fruit had severe decay symptoms and were unmarkable at the end of shelf life. These findings indicated that LDPE films were effective in preserving postharvest quality and extending shelf life of avocado fruit.